High-strength wear-resistant composite carpet material and preparation method thereof

CN122939178APending Publication Date: 2026-10-20ANHUI DEERSI CARPET CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610941062.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0008]一方面,该类胶粘层的粘结强度有限,在潮湿、高温的使用环境中,背胶易发生老化水解、发硬脆化,进而导致毯面与背衬层脱层分离,地毯边缘易出现起毛、卷边的问题,产品使用寿命与外观效果均受影响;另一方面,大量胶粘剂的使用会带来挥发性有机物与甲醛释放的风险,不符合绿色环保的使用要求,且胶黏剂的存在也导致地毯废弃后难以拆分回收,资源利用率低

Benefits of technology

本发明中通过在耐磨面层的PA6纤维基体中共混引入聚硅氧烷母粒与超细玻璃纤维粉,利用聚硅氧烷的低表面能特性,使其在熔融纺丝成型过程中自发迁移至纤维表面形成纳米级连续自润滑膜层,从纤维本征结构层面将动态摩擦系数大大降低,同时分散于基体内部的超细玻璃纤维粉可有效提升纤维的拉伸强度与抗弯折疲劳性能,从根源上减少绒头在长期摩擦踩踏下的倒伏、断裂与脱落,突破了传统表面涂覆耐磨处理易磨损脱落、耐久性差的技术局限,使材料经万转威斯博克耐磨测试后的绒头质量损失率降低,耐磨使用寿命较普通地毯大幅提升;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_17
    Figure SMS_17
Patent Text Reader

Abstract

This invention discloses a high-strength and wear-resistant composite carpet material and its preparation method, belonging to the field of carpet composite material technology. The composite carpet material of this invention is integrally formed from bottom to top through hot-melt and hot-press molding, sequentially comprising an anti-slip bottom layer, a reinforcing skeleton layer, a cushioning and rebound layer, and a wear-resistant top layer. The wear-resistant top layer is made of PA6 bulked filament tufted fibers modified by blending polysiloxane masterbatch and ultrafine glass fiber powder. After spinning, the siloxane component migrates to the fiber surface to form a self-lubricating film. Its preparation method includes six core processes: modified BCF yarn granulation and spinning, carpet tufting weaving, pre-treatment of the fabric backing adhesive, mesh skeleton laying, multi-layer synchronous hot-pressing composite, cooling embossing, and winding. This invention effectively solves the pain points of traditional carpets—poor wear resistance, easy delamination between layers, shrinkage and curling in high-temperature and humid environments, insufficient anti-slip force, and difficulty in balancing environmental protection and functionality—through the synergistic effect of three innovative technologies: in-situ self-lubricating modification of fibers, hot-melt skeleton composite, and biomimetic negative pressure anti-slip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carpet material preparation technology, and in particular to a high-strength and wear-resistant composite carpet material and its preparation method. Background Technology

[0002] As public buildings, commercial office spaces, and various indoor settings continue to demand higher performance from flooring materials, carpets have become widely used due to their advantages such as cushioning and noise reduction, comfortable feel, and strong decorative properties.

[0003] Currently, carpet products on the market are mainly divided into three categories: tufted carpets, machine-woven carpets, and non-woven carpets. Among them, multi-layer composite carpets combine performance and comfort by layering different functional layers, and are the mainstream product form for carpets in commercial settings.

[0004] In actual long-term use, the wear resistance of existing composite carpets generally has significant shortcomings. The carpet surface of traditional carpets is mostly made of ordinary polypropylene or polyamide fibers. Under dynamic friction conditions such as being rolled by office chair wheels and being stepped on by high-frequency traffic, the surface pile is prone to flattening, bending, fatigue breakage, or even complete shedding, resulting in the carpet surface exposing the substrate and greatly shortening the service life of the carpet.

[0005] To improve abrasion resistance, some existing technologies use abrasion-resistant coatings on the fiber surface. However, the surface coating is prone to wear and peeling off under continuous friction, resulting in insufficient abrasion resistance and durability, making it difficult to adapt to high-wear commercial scenarios. Other technologies increase strength by adding a large amount of hard filler to the fiber matrix, but this results in a stiff and rough fiber feel, significantly reducing the carpet's tactile feel and comfort.

[0006] At the same time, there is an irreconcilable contradiction between the interlayer structural stability and environmental performance of existing composite carpets.

[0007] To improve comfort and cushioning, most composite carpets have a sponge or polyurethane foam backing layer underneath the carpet surface, and the layers are usually bonded together with water-based adhesives, styrene-butadiene latex, or other adhesives.

[0008] On the one hand, the bonding strength of this type of adhesive layer is limited. In humid and high-temperature environments, the adhesive is prone to aging, hydrolysis, hardening, and embrittlement, leading to delamination between the carpet surface and the backing layer. This results in problems such as pilling and curling at the carpet edges, affecting both product lifespan and appearance. On the other hand, the use of large amounts of adhesives poses a risk of releasing volatile organic compounds and formaldehyde, failing to meet green and environmentally friendly usage requirements. Furthermore, the presence of adhesives makes it difficult to disassemble and recycle the carpet after disposal, resulting in low resource utilization. In addition, some products incorporate rigid reinforcing materials to improve dimensional stability, but this not only destroys the soft feel of the carpet but also fails to fundamentally solve the problems of interlayer delamination and high-temperature shrinkage and curling.

[0009] In terms of anti-slip performance, the anti-slip bottom layer of existing carpets mostly adopts a flat structure, raised dots, or striped structure design. This type of structure relies solely on the friction of the material itself to achieve anti-slip, which has limited grip on smooth surfaces such as tiles and stone. It is prone to slipping when subjected to external forces, posing a safety hazard. Furthermore, some anti-slip coatings also rely on adhesives for application and molding, further exacerbating environmental and odor issues. At the same time, the raised structure easily accumulates dust and debris, increasing the difficulty of daily cleaning and maintenance.

[0010] Therefore, this application proposes a high-strength and wear-resistant composite carpet material and its preparation method. Summary of the Invention

[0011] One objective of this invention is to propose a high-strength and wear-resistant composite carpet material and its preparation method. This invention achieves in-situ self-lubrication of fibers by blending and modifying PA6 yarn, fundamentally reducing friction loss and improving the pile's resistance to breakage and shedding. It utilizes a solvent-free hot-melt composite process with an impregnated hot-melt adhesive polyester mesh skeleton to form a riveted interlayer anchoring structure, significantly improving peel strength and suppressing shrinkage and curling issues in high-temperature and humid environments. Combined with a hexagonal micro-dimpled biomimetic anti-slip bottom layer that enhances ground grip through negative pressure adsorption, the entire preparation process does not use solvent-based adhesives, has no formaldehyde or high VOC emissions, and the all-thermoplastic material system supports recycling and reuse. It can simultaneously achieve multiple advantages such as high strength and wear resistance, strong interlayer bonding, dimensional stability, low odor and environmental friendliness, anti-slip and easy cleaning, making it suitable for high-load usage scenarios such as high-frequency foot traffic in commercial settings, office roller pressure, and automotive interiors.

[0012] According to an embodiment of the present invention, a high-strength and wear-resistant composite carpet material is formed from bottom to top by hot pressing and hot melting to create an integral structure consisting of an anti-slip bottom layer, a reinforcing skeleton layer, a cushioning and rebound layer, and a wear-resistant surface layer. The wear-resistant surface layer is a carpet structure formed by tufting modified PA6 bulk filaments. The matrix of the modified PA6 bulk filaments contains self-lubricating modified components and flame-retardant reinforcing fillers. The buffer and rebound layer is a low-odor thermoplastic polyurethane foam layer; the reinforcing skeleton layer is a polyester filament mesh impregnated with reactive hot melt adhesive. The anti-slip bottom layer is a thermoplastic elastomer layer with added halogen-free flame retardant, and its surface facing away from the reinforcing skeleton layer is provided with biomimetic anti-slip texture.

[0013] Furthermore, by weight, the raw material components of the modified PA6 expanded filament include: 70-80 parts of PA6 chips, 5-10 parts of polysiloxane masterbatch, 3-5 parts of ultrafine glass fiber powder, 0.2-1 parts of antioxidant, and 2-6 parts of halogen-free nitrogen flame retardant. After spinning, the effective components in the polysiloxane masterbatch migrate to the fiber surface to form a continuous self-lubricating film.

[0014] Furthermore, the buffer rebound layer is a physically foamed closed-cell thermoplastic polyurethane foam sheet with a density of [density missing]. The foamed sheet contains phosphorus-based environmentally friendly flame retardants. The buffer rebound layer does not contain any chemical foaming agents or organic solvents, and its VOC emission level meets the standards for automotive interior materials.

[0015] Furthermore, the polyester filament mesh fabric of the reinforcing skeleton layer has a warp and weft density of 10-20 threads / cm, and both sides of the mesh fabric are impregnated with low-melting-point polyurethane hot melt adhesive; during the hot-pressing composite process, the hot melt adhesive melts and penetrates into the root of the carpet fibers and the interior of the buffer and rebound layer, and forms an interlayer rivet joint structure after cooling.

[0016] Furthermore, the biomimetic anti-slip texture of the anti-slip bottom layer is an array of hexagonal micro-pit structures, with a depth of 0.3-1mm for a single pit and a center-to-center distance of 2-5mm between adjacent pits; the thermoplastic elastomer is a blend of thermoplastic polyester elastomer and styrene-based thermoplastic elastomer, and the halogen-free flame retardant is a system of melamine cyanurate and ammonium polyphosphate compounded in a mass ratio of 1:1 to 2:1.

[0017] A method for preparing a high-strength, wear-resistant composite carpet material includes the following steps: S1. Preparation of modified yarn: PA6 chips are vacuum dried to a moisture content of less than 500 ppm, and then mixed with polysiloxane masterbatch, ultrafine glass fiber powder, halogen-free nitrogen flame retardant and antioxidant at high speed according to the ratio. The mixture is then fed into a twin-screw extruder for co-extrusion granulation to obtain modified polyamide masterbatch. The modified polyamide masterbatch is then fed into a BCF spinning machine for melt spinning. After multi-stage drawing, crimping and heat setting, modified PA6 bulk filament is obtained. S2. Blanket weaving: The modified PA6 bulky filaments obtained in step S1 are woven into the polypropylene base fabric through a tufting machine, and the pile height is controlled to be 3-8mm to obtain the blanket fabric. S3. Adhesive Pretreatment: A layer of reactive polyurethane hot melt adhesive is evenly coated onto the back of the carpet fabric using a roller coating method. The coating amount is controlled to be... ; S4. Laying the skeleton layer: Lay the polyester filament mesh pre-impregnated with low melting point polyurethane hot melt adhesive flat on the back of the coated carpet fabric to remove air bubbles between layers. S5. Lamination and hot pressing: Thermoplastic polyurethane foam sheets and anti-slip bottom blanks are stacked on top of the laid mesh cloth, and the whole is fed into a double belt laminator for continuous hot pressing and bonding, so that each layer melts and bonds to form a whole. S6. Post-forming treatment: The hot-pressed composite material is sent to the cooling section for shaping, and then a patterned roller is used to press a biomimetic anti-slip texture onto the surface of the anti-slip bottom layer. Finally, the finished product is obtained by trimming the edges and winding it up.

[0018] Furthermore, in step S1, the extrusion temperature of each section of the twin-screw extruder is 240–270°C; the spinning box temperature of the melt spinning process is 260–280°C; the total draw ratio is 2.5–3.5 times; the crimp count is controlled at 15–25 crimps / cm; and the heat setting temperature is 120–150°C.

[0019] Furthermore, in step S5, the hot pressing temperature of the dual-belt laminator is set to 150-180°C, the hot pressing pressure is 3-5 MPa, and the residence time of the material in the hot pressing section is 30-90 seconds.

[0020] Furthermore, in step S4, the pre-impregnation process of the polyester filament mesh fabric is as follows: the mesh fabric is continuously passed through a molten low-melting-point polyurethane hot melt adhesive bath, and the amount of adhesive applied to one side is controlled by roller extrusion. After cooling to room temperature, roll it up for later use.

[0021] Furthermore, in step S6, the cooling and shaping temperature is 20-35°C, and the cooling time is 1-3 minutes.

[0022] The beneficial effects of this invention are: In this invention, polysiloxane masterbatch and ultrafine glass fiber powder are co-introduced into the PA6 fiber matrix of the wear-resistant surface layer. Utilizing the low surface energy of polysiloxane, it spontaneously migrates to the fiber surface during melt spinning to form a nanoscale continuous self-lubricating film layer. This significantly reduces the dynamic friction coefficient from the intrinsic fiber structure level. At the same time, the ultrafine glass fiber powder dispersed inside the matrix effectively improves the tensile strength and bending fatigue resistance of the fiber, fundamentally reducing the collapse, breakage, and shedding of the pile under long-term friction and trampling. This overcomes the technical limitations of traditional surface coating wear-resistant treatments, which are prone to wear and detachment and have poor durability. The pile mass loss rate is reduced after the material undergoes a 10,000-revolution Wisbock abrasion resistance test, and the wear-resistant service life is significantly improved compared to ordinary carpets. Furthermore, using polyester filament mesh pre-impregnated with low-melting-point hot melt adhesive as the reinforcing skeleton layer, the molten hot melt adhesive can penetrate bidirectionally into the fiber roots of the carpet and the surface pores of the buffer and rebound layer during the hot-pressing composite process. After cooling and solidification, it forms a riveted mechanical anchoring structure, increasing the interlayer peel strength to over 100N / 3cm. This completely solves the defects of traditional adhesive carpets such as adhesive aging and hydrolysis, interlayer separation, and edge lifting in humid and high-temperature environments. At the same time, the polyester mesh fabric, as the overall load-bearing skeleton, can control the material's warp and weft thermal shrinkage rate to below 0.2%, significantly improving the product's dimensional stability. Moreover, the entire production process is solvent-free, eliminating the risk of VOC and formaldehyde release from the source. Combined with the PA, TPU, and PET thermoplastic material system, the product is recyclable and reusable, effectively resolving the inherent contradiction between the functional improvement of traditional carpets and environmental protection requirements. The anti-slip bottom layer adopts an array of hexagonal micro-dimples with a biomimetic structure. By utilizing the adsorption mechanism of creating local negative pressure by expelling air from the dimples under pressure, it significantly increases the static friction coefficient between the carpet and the smooth base surface. The anti-slip effect is far superior to conventional flat, dotted, or striped anti-slip structures. Moreover, the dimple structure does not easily accumulate dust and debris, balancing excellent anti-slip performance with convenient daily cleaning. These three innovative features work together to create a composite carpet system that is high-strength, wear-resistant, has stable interlayer structure, is dimensionally stable, low-odor, environmentally friendly, and has excellent anti-slip performance. This breaks through the performance bottleneck of existing technologies and can be widely adapted to commercial high-wear scenarios and various application scenarios with strict requirements for environmental protection and odor control. Attached Figure Description

[0023] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the overall structure of a high-strength and wear-resistant composite carpet material proposed in this invention. Figure 2 This is a flowchart illustrating a method for preparing a high-strength, wear-resistant composite carpet material proposed in this invention. Detailed Implementation

[0024] To make the technical means and objectives and effects of the present invention easier to understand, the embodiments of the present invention will be described in detail below with reference to specific illustrations.

[0025] like Figure 1As shown, this invention discloses a high-strength and wear-resistant composite carpet material, which consists of an anti-slip bottom layer, a reinforcing skeleton layer, a cushioning and rebound layer, and a wear-resistant top layer, formed as a single integrated structure through hot-pressing and hot-melt bonding from bottom to top. This material, through the synergistic effect of in-situ fiber modification, skeleton layer reinforcement, and solvent-free hot-melt bonding, simultaneously solves several problems of traditional carpets, including insufficient wear resistance, easy delamination between layers, poor environmental performance, and poor dimensional stability. It is suitable for high-intensity applications such as commercial offices, public places, and automotive interiors.

[0026] The wear-resistant surface layer is a carpet structure formed by tufting modified PA6 bulked filaments, and the pile height can be adjusted within the range of 3 to 8 mm depending on the application scenario.

[0027] This modified expanded filament uses PA6 chips as the matrix resin. Self-lubricating modifying components and flame-retardant reinforcing fillers are dispersed in the matrix through blending modification. During melt spinning, the low surface energy polysiloxane component gradually migrates to the fiber surface with the melt flow. After spinning and cooling, a continuous self-lubricating film layer with a nanometer thickness can be formed on the fiber surface, reducing the dynamic friction coefficient of the fiber by more than 30%, and significantly reducing the wear and flattening of the fibers during repeated stepping and friction.

[0028] Meanwhile, the ultrafine glass fiber powder dispersed inside the fiber matrix can significantly improve the tensile strength and bending fatigue resistance of the fiber, reduce the problem of pile breakage and shedding, and extend the overall service life of the carpet.

[0029] By weight, the raw material components of modified PA6 expanded filament include 70-80 parts PA6 chips, 5-10 parts polysiloxane masterbatch, 3-5 parts ultrafine glass fiber powder, and 0.2-1 parts antioxidant. 2-6 parts of halogen-free nitrogen-based flame retardant can also be added according to flame retardant requirements.

[0030] The polysiloxane masterbatch uses PA6 as a carrier, with an effective siloxane content of no less than 50% to ensure compatibility with the matrix resin and avoid phase separation and fiber breakage during spinning. The particle size of the ultrafine glass fiber powder is controlled between 5 and 20 μm, which can be uniformly dispersed in the melt and will not clog the spinneret.

[0031] The cushioning and rebound layer uses a low-odor thermoplastic polyurethane foam layer, specifically a closed-cell thermoplastic polyurethane foam sheet prepared through a physical foaming process, with a density controlled at [specific value missing]. .

[0032] This foam layer replaces the chemically foamed polyurethane soft foam and sponge backing used in traditional carpets. No chemical foaming agents or organic solvents are added during the production process, resulting in extremely low volatile organic compound release and no irritating odor in the finished product, meeting stringent environmental standards.

[0033] Closed-cell foam sheets have excellent resilience and resistance to compression set. They provide ample cushioning when stepped on, quickly return to their original shape after being unloaded, and are not prone to collapse or deformation under long-term, high-frequency use.

[0034] Phosphorus-based environmentally friendly flame retardants can be dispersed and added inside the foamed sheet to improve the overall flame retardancy rating of the material without damaging the foam structure.

[0035] Because thermoplastic polyurethane itself has hot-melt bonding properties, during the hot-pressing composite process, the upper and lower surfaces of the foamed sheet can undergo micro-melting, forming an interface bond with the upper and lower layer materials, further strengthening the interlayer bonding strength.

[0036] The reinforcing skeleton layer is a polyester filament mesh impregnated with reactive hot melt adhesive, embedded between the cushioning and rebound layer and the abrasion-resistant surface layer, serving as the load-bearing reinforcing skeleton of the entire composite structure.

[0037] Polyester filament mesh fabric has extremely high tensile strength and extremely low heat shrinkage rate, which can bear the main tensile force in the warp and weft directions of the carpet, effectively suppress the shrinkage and deformation of the material in high temperature and humid environment, and improve the overall dimensional stability; the warp and weft density of the mesh fabric is 10 to 20 threads / cm, and the mesh aperture is uniform, which can ensure that the hot melt adhesive can fully penetrate through.

[0038] Both sides of the mesh fabric are pre-impregnated with low-melting-point polyurethane hot melt adhesive, with the amount of adhesive applied to each side controlled within a specified range. During the hot-pressing process, the hot melt adhesive melts when heated and can penetrate upwards to the fiber roots of the carpet fabric, filling the gaps between the fibers. After cooling and solidification, it forms an anchoring structure similar to a rivet, firmly locking the carpet fibers to the skeleton layer and preventing the pile from being pulled out and falling off. It can also penetrate downwards into the surface pores of the buffer and rebound layer, forming a mechanical interlocking structure with the foaming material, which greatly improves the peel strength between the layers.

[0039] By embedding this reinforced skeleton layer, the thermal shrinkage rate of the carpet material in both the warp and weft directions can be reduced to below 0.2%, fundamentally solving the problems of traditional carpets being prone to curling and peeling.

[0040] The anti-slip bottom layer is located at the bottom of the material and is made of thermoplastic elastomer material with added halogen-free flame retardant through hot pressing. The side of the bottom layer facing away from the reinforcing skeleton layer is provided with biomimetic anti-slip texture.

[0041] The thermoplastic elastomer is prepared by blending thermoplastic polyester elastomer with styrene-based thermoplastic elastomer, which takes into account excellent wear resistance, flexibility and hot melt bonding performance, and can form a strong interfacial bond with the buffer and rebound layer above.

[0042] The preferred halogen-free flame retardant is a system of melamine cyanurate and ammonium polyphosphate compounded in a mass ratio of 1:1 to 2:1. This system improves the flame retardancy rating without producing toxic or harmful fumes, thus meeting environmental protection requirements for flame retardancy.

[0043] The biomimetic anti-slip texture on the bottom surface consists of an array of hexagonal micro-dimples, each with a depth of 0.3–1 mm and a center-to-center distance of 2–5 mm between adjacent dimples. When the carpet is subjected to foot pressure, the air inside the dimples is quickly expelled, creating a localized negative pressure adsorption effect. This significantly improves the static friction between the carpet and the smooth surface. Compared to traditional flat, dotted, or striped anti-slip structures, the negative pressure adsorption effect of the hexagonal dimples is more uniform, improving anti-slip performance by more than 40%. Furthermore, the dimple structure does not easily accumulate dust and debris, making daily cleaning more convenient.

[0044] like Figure 2 As shown, this invention also discloses a method for preparing a high-strength, wear-resistant composite carpet material, comprising the following steps: S1. First, the modified yarn is prepared by placing PA6 chips in a vacuum drying equipment and drying them at a temperature of 80-100℃ for 8-12 hours. The moisture content of the chips is controlled below 500ppm to avoid the formation of bubbles in the melt during the subsequent spinning process, which could lead to yarn breakage.

[0045] The dried PA6 chips are added to a high-speed mixer in proportion to polysiloxane masterbatch, ultrafine glass fiber powder, antioxidant and optional flame retardant, and mixed at 800-1200 rpm for 5-10 minutes to ensure that the components are fully dispersed and uniform.

[0046] The uniformly mixed material is fed into a twin-screw extruder for co-extrusion granulation. The extrusion temperature of each section of the twin-screw extruder is controlled within the range of 240-270℃ along the feeding direction, and the screw speed is 200-300 rpm. The extruded melt strip is cooled by cooling water and then sent to a pelletizer for pelletizing to obtain modified polyamide masterbatch.

[0047] After the modified polyamide masterbatch is dried again, it is fed into a BCF spinning machine for melt spinning. The temperature of the spinning box is controlled at 260-280℃. The melt is extruded through the spinneret to form nascent fibers, which are then drawn through multiple stages of hot rollers with a total draw ratio controlled at 2.5-3.5 times. The drawn fibers are then mechanically crimped in a crimping box with a crimp count controlled at 15-25 crimps / cm. Finally, the fibers are heat-set at 120-150℃ to obtain modified PA6 bulk filaments.

[0048] S2. After completing the yarn preparation, the carpet surface is woven. The modified PA6 bulky filament is used as the pile yarn and woven into the polypropylene base fabric through a tufting device. During the weaving process, the pile height is controlled to be 3-8mm. The stitch length and row spacing are adjusted according to the carpet density requirements. After the weaving is completed, the carpet surface fabric is obtained. The pile can be trimmed according to product requirements to form different styles of carpet surface effects.

[0049] S3. Subsequently, a backing adhesive pretreatment is performed. A layer of reactive polyurethane hot melt adhesive is evenly coated onto the base fabric side of the carpet using a roller coating machine. The coating amount is controlled to be... The pre-applied hot melt adhesive can initially fix the pile of the carpet, preventing the pile from shifting or falling off in subsequent processes. At the same time, it can fully melt and fuse with the hot melt adhesive of the subsequent skeleton layer, improving the overall bonding.

[0050] S4. After the backing adhesive is applied, the skeleton layer is laid. The pre-impregnated polyester filament mesh is laid flat on the back of the coated carpet fabric. During the laying process, the mesh tension is kept uniform to avoid defects such as wrinkles and skewing. At the same time, the air bubbles remaining between the layers are removed by rolling with a light pressure roller to ensure that the two layers are tightly bonded.

[0051] The pre-impregnation process for the polyester filament mesh fabric is as follows: The rolled polyester mesh fabric is continuously passed through a glue tank containing molten low-melting-point polyurethane hot melt adhesive at a constant speed, ensuring the fiber surface of the mesh fabric is fully impregnated with the adhesive. Subsequently, it is passed through a pair of adjustable-pitch extrusion rollers to control the amount of adhesive applied to one side of the mesh fabric. Excess adhesive is scraped off and returned to the adhesive tank. The impregnated mesh is cooled and shaped by cooling rollers and then rolled up for later use.

[0052] S5. After the skeleton layer is laid, the layered hot-press composite is carried out. Thermoplastic polyurethane foam sheets and anti-slip bottom blanks are stacked on top of the laid mesh cloth to form a four-layer stacked blank structure. The stacked blanks are fed into the double belt laminator at a uniform speed for continuous hot-press composite.

[0053] The dual-belt laminator is divided into a preheating section, a hot pressing section, and a cooling section. The temperature of the hot pressing section is set at 150-180℃, the hot pressing pressure is controlled at 3-5MPa, and the residence time of the billet in the hot pressing section is 30-90 seconds.

[0054] Under high temperature and pressure, the hot melt adhesive and thermoplastic material at the interface of each layer melt together. The adhesive fully penetrates into the fiber gaps and material pores on both sides. After cooling and solidification, it forms a strong mechanical interlocking and bonding bond, making the four-layer structure fuse into a complete whole. No additional solvent-based adhesive is needed, and there is no emission of volatile organic compounds during the production process.

[0055] S6. Finally, after molding, the hot-pressed composite material enters the cooling section of the laminator for cooling and shaping. The temperature of the cooling section is controlled at 20-35℃, and the cooling time is 1-3 minutes to allow the material to cool and solidify fully, so as to avoid deformation during subsequent processing and use.

[0056] After the material is shaped, it is pressed onto the lower surface of the anti-slip base layer by a patterned roller with a hexagonal punch structure, creating an array of hexagonal micro-pits for anti-slip texture. Finally, the rough edges on both sides are trimmed by an edge trimming device, and the material is rolled up to the specified length and width to obtain the finished high-strength wear-resistant composite carpet material.

[0057] Example 1

[0058] This embodiment provides a high-strength and wear-resistant composite carpet material, which is prepared according to the following steps: S1. Preparation of modified yarn: Weigh 75 parts of PA6 chips, 8 parts of polysiloxane masterbatch, 4 parts of ultrafine glass fiber powder, 0.5 parts of antioxidant, and 4 parts of halogen-free nitrogen flame retardant according to the following weight proportions: After vacuum drying the PA6 chips to a moisture content of 400 ppm, mix them evenly with the remaining components in a high-speed mixer, and then granulate them by blending in a twin-screw extruder. The extrusion temperatures along the feed direction are 245℃, 255℃, 265℃, and 260℃, and the screw speed is 250 rpm. Then, feed the modified masterbatch into a BCF spinning machine for melt spinning. The spinning box temperature is 270℃, the total draw ratio is 3.0 times, the crimp count is 20 crimps / cm, and the heat setting temperature is 135℃ to obtain modified PA6 bulked filament.

[0059] S2. Blanket weaving: Modified bulky filaments are woven into polypropylene base fabric through a tufting machine, and the pile height is controlled to be 5mm to obtain the blanket fabric.

[0060] S3. Adhesive pretreatment: A reactive polyurethane hot melt adhesive is roller-coated onto the back of the fabric, with an adhesive application amount of [amount missing]. .

[0061] S4. Reinforcement Layer Laying: A polyester filament mesh with a warp and weft density of 15 threads / cm is used, pre-impregnated with low-melting-point polyurethane hot melt adhesive, with a single-sided adhesive application rate of [missing information]. Lay the mesh fabric flat on the back of the raw fabric and roll it to release air.

[0062] S5, Lamination and Hot-Pressure Composite: Layers of materials with a density of [density missing] are sequentially stacked on top of the mesh fabric. The thermoplastic polyurethane foam sheet and the thermoplastic elastomer anti-slip base blank are fed into a double belt laminator. The hot pressing temperature is set at 165℃, the hot pressing pressure is 4MPa, and the hot pressing time is 60 seconds.

[0063] S6. Post-forming treatment: Cool and set at 30℃ for 2 minutes, then press hexagonal micro-pits on the surface of the anti-slip bottom layer using patterned rollers. The pit depth is 0.6mm and the center-to-center distance between adjacent pits is 3mm. Finally, trim the edges and roll up to obtain the finished product.

[0064] Example 2

[0065] The preparation process in this embodiment is basically the same as that in Example 1, with only the raw material ratio and process parameters being adjusted: The modified yarn raw materials, by weight, are: 70 parts PA6 chips, 5 parts polysiloxane masterbatch, 3 parts ultrafine glass fiber powder, 0.2 parts antioxidant, and 2 parts halogen-free nitrogen-based flame retardant; melt spinning temperature is 260℃, total draw ratio is 2.5 times, crimp count is 15 crimps / cm, and heat setting temperature is 120℃. The pile height of the carpet surface is controlled at 3mm, and the amount of adhesive applied to the backing is... It uses polyester mesh fabric with a warp and weft density of 10 threads / cm, and single-sided adhesive application. The density of thermoplastic polyurethane foam sheets is Hot pressing temperature: 150℃; hot pressing pressure: 3MPa; hot pressing time: 30 seconds; anti-slip texture pit depth: 0.3mm; center-to-center distance between adjacent pits: 2mm.

[0066] Example 3

[0067] The preparation process in this embodiment is basically the same as that in Example 1, with only the raw material ratio and process parameters being adjusted: The modified yarn raw materials, by weight, are: 80 parts PA6 chips, 10 parts polysiloxane masterbatch, 5 parts ultrafine glass fiber powder, 1 part antioxidant, and 6 parts halogen-free nitrogen-based flame retardant; melt spinning temperature is 280℃, total draw ratio is 3.5 times, crimp count is 25 crimps / cm, and heat setting temperature is 150℃. The pile height of the carpet surface is controlled at 8mm, and the amount of adhesive applied to the backing is... It uses polyester mesh fabric with a warp and weft density of 20 threads / cm, and has adhesive on one side. The density of thermoplastic polyurethane foam sheets is Hot pressing temperature: 180℃; hot pressing pressure: 5MPa; hot pressing time: 90 seconds; anti-slip texture pit depth: 1mm; center-to-center distance between adjacent pits: 5mm.

[0068] Example 4

[0069] This embodiment is a comparative example, using traditional processes to prepare ordinary PA6 composite carpets: the surface layer is made of unmodified ordinary PA6 bulked filament tufted pile with a pile height of 5mm, the backing is made of water-based styrene-butadiene latex coated composite polyurethane sponge backing, without a reinforcing skeleton layer, and the bottom layer is a thermoplastic elastomer anti-slip layer with a normal flat structure.

[0070] The above four groups of samples were subjected to performance tests according to the corresponding standards. The test items included interlayer peel strength, abrasion resistance, heat shrinkage rate, anti-slip performance, and odor level. The test results are shown in Table 1 below:

[0071] As can be seen from the above test data, the composite carpet material prepared using the technical solution of this invention has significantly better performance than products made using traditional processes.

[0072] Among them, the mass loss rate after 10,000 revolutions of abrasion resistance test is less than 0.5%, and the abrasion resistance performance is improved by more than 3 times, which can meet the long-term use needs of commercial high-wear scenarios; the interlayer peel strength reaches more than 100N / 3cm, which is more than 50% higher than traditional products, effectively solving the problems of carpet easy delamination and edge curling; the warp and weft heat shrinkage rates are less than 0.2%, and it can still maintain dimensional stability in high temperature and humid environment, and is not easy to curl and deform; at the same time, the odor level of the products is less than 3.0, there is no solvent volatilization in the production process, and the overall environmental protection performance is excellent, which can meet the stringent environmental protection requirements of high-end commercial spaces and automotive interiors.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-strength, wear-resistant composite carpet material, characterized in that, From bottom to top, the anti-slip bottom layer, the reinforcing skeleton layer, the buffer and rebound layer, and the wear-resistant surface layer are formed into an integral structure through hot pressing and hot melting. The wear-resistant surface layer is a carpet structure formed by tufting modified PA6 bulk filaments. The matrix of the modified PA6 bulk filaments contains self-lubricating modified components and flame-retardant reinforcing fillers. The buffer and rebound layer is a low-odor thermoplastic polyurethane foam layer; the reinforcing skeleton layer is a polyester filament mesh impregnated with reactive hot melt adhesive. The anti-slip bottom layer is a thermoplastic elastomer layer with added halogen-free flame retardant, and its surface facing away from the reinforcing skeleton layer is provided with biomimetic anti-slip texture.

2. The high-strength and wear-resistant composite carpet material according to claim 1, characterized in that, The raw material components of the modified PA6 expanded filament, by weight, include: 70-80 parts of PA6 chips, 5-10 parts of polysiloxane masterbatch, 3-5 parts of ultrafine glass fiber powder, 0.2-1 parts of antioxidant, and 2-6 parts of halogen-free nitrogen flame retardant. After spinning, the effective components in the polysiloxane masterbatch migrate to the fiber surface to form a continuous self-lubricating film.

3. The high-strength and wear-resistant composite carpet material according to claim 1, characterized in that, The buffer rebound layer is a closed-cell thermoplastic polyurethane foam sheet formed by physical foaming, with a density of [density missing]. The foamed sheet contains phosphorus-based environmentally friendly flame retardants. The buffer rebound layer does not contain any chemical foaming agents or organic solvents, and its VOC emission level meets the standards for automotive interior materials.

4. The high-strength and wear-resistant composite carpet material according to claim 1, characterized in that, The polyester filament mesh fabric of the reinforcing skeleton layer has a warp and weft density of 10-20 threads / cm, and both sides of the mesh fabric are impregnated with low melting point polyurethane hot melt adhesive. During the hot pressing process, the hot melt adhesive melts and penetrates into the root of the carpet fibers and the interior of the buffer and rebound layer, and forms an interlayer rivet joint structure after cooling.

5. The high-strength and wear-resistant composite carpet material according to claim 1, characterized in that, The biomimetic anti-slip texture of the anti-slip bottom layer is an array of hexagonal micro-pit structures, with a depth of 0.3-1mm for a single pit and a center-to-center distance of 2-5mm between adjacent pits; the thermoplastic elastomer is a blend of thermoplastic polyester elastomer and styrene-based thermoplastic elastomer; and the halogen-free flame retardant is a system of melamine cyanurate and ammonium polyphosphate compounded in a mass ratio of 1:1 to 2:

1.

6. A method for preparing a high-strength, wear-resistant composite carpet material according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Preparation of modified yarn: PA6 chips are vacuum dried to a moisture content of less than 500 ppm, and then mixed with polysiloxane masterbatch, ultrafine glass fiber powder, halogen-free nitrogen flame retardant and antioxidant at high speed according to the ratio. The mixture is then fed into a twin-screw extruder for co-extrusion granulation to obtain modified polyamide masterbatch. The modified polyamide masterbatch is then fed into a BCF spinning machine for melt spinning. After multi-stage drawing, crimping and heat setting, modified PA6 bulk filament is obtained. S2. Blanket weaving: The modified PA6 bulky filaments obtained in step S1 are woven into the polypropylene base fabric through a tufting machine, and the pile height is controlled to be 3-8mm to obtain the blanket fabric. S3. Adhesive Pretreatment: A layer of reactive polyurethane hot melt adhesive is evenly coated onto the back of the carpet fabric using a roller coating method. The coating amount is controlled to be... ; S4. Laying the skeleton layer: Lay the polyester filament mesh pre-impregnated with low melting point polyurethane hot melt adhesive flat on the back of the coated carpet fabric to remove air bubbles between layers. S5. Lamination and hot pressing: Thermoplastic polyurethane foam sheets and anti-slip bottom blanks are stacked on top of the laid mesh cloth, and the whole is fed into a double belt laminator for continuous hot pressing and bonding, so that each layer melts and bonds to form a whole. S6. Post-forming treatment: The hot-pressed composite material is sent to the cooling section for shaping, and then a patterned roller is used to press a biomimetic anti-slip texture onto the surface of the anti-slip bottom layer. Finally, the finished product is obtained by trimming the edges and winding it up.

7. The method for preparing a high-strength, wear-resistant composite carpet material according to claim 6, characterized in that, In step S1, the extrusion temperature of each section of the twin-screw extruder is 240-270℃; the spinning box temperature of melt spinning is 260-280℃, the total draw ratio is 2.5-3.5 times, the crimp number is controlled at 15-25 crimps / cm, and the heat setting temperature is 120-150℃.

8. The method for preparing a high-strength, wear-resistant composite carpet material according to claim 6, characterized in that, In step S5, the hot pressing temperature of the dual-belt laminator is set to 150-180℃, the hot pressing pressure is 3-5MPa, and the residence time of the material in the hot pressing section is 30-90 seconds.

9. The method for preparing a high-strength, wear-resistant composite carpet material according to claim 6, characterized in that, In step S4, the pre-impregnation process of the polyester filament mesh fabric is as follows: The mesh fabric is continuously passed through a molten low-melting-point polyurethane hot melt adhesive bath, and the amount of adhesive applied to each side is controlled by roller extrusion. After cooling to room temperature, roll it up for later use.

10. The method for preparing a high-strength, wear-resistant composite carpet material according to claim 6, characterized in that, In step S6, the cooling and shaping temperature is 20-35°C, and the cooling time is 1-3 minutes.